Studies of Valmiki National Park, Bihar with Reference to ecological Conservation: Studies of Valmiki National Park, Bihar with Reference to ecological Conservation - Singh, Ravindra K. (International Journal of Pharmaceutical & Biological Archive, 2018)
Judicious manipulation and conservation of habitat will increase the carrying capacities of the reserve area. Carrying capacity of dense forest is always little. Hence, the habitat of forest needs manipulation in a manner that forest is always kept at a minimum utilization during the different periods of the year. Habitat manipulation and conservation should always be done to benefit all wild animals without causing much disturbance to them. It includes conservation of soil and water, development of new water sources, improvement of food and cover, and control of grazing.